2019
DOI: 10.1111/ijcp.13394
|View full text |Cite
|
Sign up to set email alerts
|

Association of intra‐operative hypotension with acute kidney injury, myocardial injury and mortality in non‐cardiac surgery: A meta‐analysis

Abstract: Background Intra‐operative hypotension might induce poor postoperative outcomes in non‐cardiac surgery, and the relationship between the level or duration of Intra‐operative hypotension (IOH) and postoperative adverse events is still unclear. In this study, we performed a meta‐analysis to determine how IOH could affect acute kidney injury (AKI), myocardial injury and mortality in non‐cardiac surgery. Methods We searched PubMed (Medline), Embase, Springer, The Cochrane Library, Ovid and Google Scholar, and retr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 36 publications
1
21
0
1
Order By: Relevance
“…Multiple large retrospective studies have shown an association between IOH and postoperative AKI, [13][14][15][16][17][18][19][20]22] and others have reported an association between the duration of IOH and cardiac, renal and neurological adverse events. [13,17,23,24] However, this association remains poorly de ned in the context of liver transplantation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple large retrospective studies have shown an association between IOH and postoperative AKI, [13][14][15][16][17][18][19][20]22] and others have reported an association between the duration of IOH and cardiac, renal and neurological adverse events. [13,17,23,24] However, this association remains poorly de ned in the context of liver transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9][10][11][12] Haemodynamic variable such as intraoperative hypotension (IOH), most often de ned as a mean arterial pressure (MAP) ≤ 65 mmHg, has been shown to be one of the most important factors associated with postoperative AKI. [13] Numerous large retrospective studies have shown that IOH is associated with postoperative AKI after various types of non-cardiac surgery, [14][15][16][17][18][19] but data on such an association in liver transplantation remain scarce. [20] We therefore conducted a historical cohort analysis to evaluate the association between IOH and the development of postoperative AKI in patients undergoing liver transplant surgery.…”
Section: Introductionmentioning
confidence: 99%
“…They found that IOH was associated with an increased risk of postoperative AKI and myocardial injury. In more detail, the duration of IOH lasting only more than 5 min was associated with an increased risk of 30-day mortality [21]. In particular, patients suffering from pre-existing CVDs may have increased risks of perioperative cardiovascular morbidity and mortality following noncardiac surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Episodes of intraoperative hypotension, defined as mean arterial pressure (MAP) below 60 mmHg, may decrease renal perfusion, resulting in AKI in patients with impaired autoregulation [ 54 , 55 , 56 ]. Sun demonstrated that sustained intraoperative periods of MAP less than 55 mmHg (2.34 (95% CI 1.35–4.05)) and less than 60 mmHg (OR 1.84 (95% CI 1.11 to 3.06)) were associated with postoperative AKI [ 54 ].…”
Section: Managementmentioning
confidence: 99%
“…Sun demonstrated that sustained intraoperative periods of MAP less than 55 mmHg (2.34 (95% CI 1.35–4.05)) and less than 60 mmHg (OR 1.84 (95% CI 1.11 to 3.06)) were associated with postoperative AKI [ 54 ]. Also, intraoperative hypotension for more than 1 min is significantly associated with an increased risk of postoperative AKI [ 55 ]. Thus avoidance of intraoperative hypotension could decrease the risk of AKI.…”
Section: Managementmentioning
confidence: 99%